Statistical distributions of thesauri and their uses in classification of science publications - Balys, Vaidas; Rudzkis, Rimantas (Lietuvos matematikos rinkinys, 2003)
Automatic keywords assignment is a way to solve the problem of classification of scientific information. Paper deals with idea of implementing this assignement by making use of models for distribution of scientific terms. Some analysis was carried out and on base of its results the conclusions about effectiveness, usefullnes, main shortages and the ways of refinement of simpliest algorithms are drawn. A need for better algorithms is motivated and some ideas about how to create them are proposed.